Interactive effects of triploidy induction and culture densities on growth performance and stress, immune, and metabolic responses in juvenile rainbow trout (Oncorhynchus mykiss) - Roghayeh Mahmoudi; Mahdi Naderi; Hakimeh Dopeikar; Seyed Ali Khorasaninasab; Seyed Hadi Seyedalhosseini (Aquaculture Reports)
This experiment aimed to evaluate the effects of triploidization and culture densities on the performance of rainbow trout. Juveniles (30.70 ± 1.04 g) were randomly stocked into 24 fiberglass tanks with a flow-through system. The experiment was designed with two ploidy conditions (diploid and triploid) each with 20 (40 fish/tank), 30 (59 fish/tank), 40 (79 fish/tank), and 50 (99 fish/tank) kg/m3 culture densities, a 2 × 4 factorial design. After 9 weeks, final weight, weight gain, specific growth rate, and protein efficiency ratio (PER) in fish cultured at 20, 30, and 40 kg/m3 were significantly higher and feed conversion ratio (FCR) was lower compared to those cultured at 50 kg/m3 (P < 0.05). Also, at 50 kg/m3 density, FCR in triploids was significantly higher and PER was lower compared to diploids (P < 0.05). Serum cortisol levels were highest and osmolality and total antioxidant capacity values were lowest in triploid fish cultured at the highest (50 kg/m3) density, indicating that triploids were affected more than diploids by chronic high density stress. Serum lysozyme and alternative complement (ACH50) activities and globulin content were significantly lower in fish cultured at 50 kg/m3 (P < 0.05). Thus, rainbow trout chronically exposed to high culture density (50 kg/m3) showed signs of immunosuppression. Chronic high density stress exhibited harmful impacts on liver functions, resulting in elevated activities of serum ALT and AST enzymes (P < 0.05). Also, lipid stores (cholesterol, LDL, HDL, and triglyceride) were depleted due to chronic high density stress. Overall, high density (50 kg/m3) negatively influenced fish performance, but moderate culture densities (20, 30, and 40 kg/m3) do not influence growth and stress, innate immune, and metabolic responses of fish. Thus, triploid rainbow trout juveniles can act well and be recommended to the aquaculture industry at a culture density of 40 kg/m3.